1994
DOI: 10.1002/bjs.1800810949
|View full text |Cite
|
Sign up to set email alerts
|

‘Reversible chemical sphincterotomy’ by local application of glyceryl trinitrate

Abstract: Nitric oxide has emerged as one of the most important neurotransmitters mediating internal anal sphincter relaxation. The effect of glyceryl trinitrate, a nitric oxide donor, on anal tone was examined. Maximum resting pressure, predominantly a function of the smooth muscle internal anal sphincter, was measured before and 20 min after application of 0.2 per cent glyceryl trinitrate ointment in ten patients. Pressure decreased by a mean of 27 per cent (95 per cent confidence interval 18-36 per cent) (P = 0.0004)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
99
0
4

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(108 citation statements)
references
References 31 publications
5
99
0
4
Order By: Relevance
“…Exogenous nitrates release nitric oxide in vivo and have been used clinically as nitric oxide donors. Loder et al (1994) demonstrated that topical application of 0.2% GTN led to decreased resting anal pressure. Chemical sphincterotomy using GTN with adjunctive stool softeners has been demonstrated to be quite effective at relieving symptoms and promoting healing.…”
Section: Glyceryl Trinitratementioning
confidence: 96%
“…Exogenous nitrates release nitric oxide in vivo and have been used clinically as nitric oxide donors. Loder et al (1994) demonstrated that topical application of 0.2% GTN led to decreased resting anal pressure. Chemical sphincterotomy using GTN with adjunctive stool softeners has been demonstrated to be quite effective at relieving symptoms and promoting healing.…”
Section: Glyceryl Trinitratementioning
confidence: 96%
“…A significant reduction in anal pressure after soaking in warm water has been reported [34] . Based on the theory that anal fissures are caused by ischemia through a spasmodic internal sphincter, pharmacological agents including glyceryl trinitrate (GTN) [35][36][37] , diltiazem [35,[38][39][40] , and botulinum toxin may be useful. These agents have been employed to reduce the resting anal canal pressure and to improve blood flow, and as an alternative to surgical sphincterotomy for chronic fissures.…”
Section: Treatmentmentioning
confidence: 99%
“…These agents have been employed to reduce the resting anal canal pressure and to improve blood flow, and as an alternative to surgical sphincterotomy for chronic fissures. GTN ointment applied two to four times per day to the anus has been the most extensively studied, resulting in various healing rates and the identification of a major side effect in dose-related headaches [36] . A randomized, controlled trial has shown that 0.2% nitroglycerin ointment applied twice daily healed chronic ulcers (68% compared with 8% in the placebo group) with evidence of a reduction in resting anal pressure and an increase in anoderm blood flow after eight weeks of treatment [37] .…”
Section: Treatmentmentioning
confidence: 99%
“…Loder et al and Guillemot et al showed that topical application of nitroglycerin results in the lowering of the IAS in normal human patients. 40 It was thus popularly hypothesised that GTN and other nitrates can reduce pain by relaxing the IAS. Lund and Scholefield used 0.2% GTN ointment and showed that it decreased MARP by 33% and induced an increase in anodermal blood flow.…”
Section: Gtnmentioning
confidence: 99%
“…7 It has been shown that GTN works most effectively on the upper two-thirds of the anal canal and to a lesser extent on the lower third of the anal canal [40]. Various trials have shown that topical GTN is effective in promoting healing in patients with chronic anal fissures.…”
Section: Gtnmentioning
confidence: 99%